Efficient use of data and knowledge transfers in information systems (Revista Innova Educación, 2022)
Business intelligence under data treatment is consolidated in one of the differentiating factors between organizations. Business intelligence (BI) solutions are not only applicable for commercial purposes, they are also used to measure the performance and fulfillment of goals in organizations. The objective of this research is to apply an adaptive BI model in order to diagnose the real state of the organization and formulate from it improvement plans capable of raising the levels of performance and profits of the same. The application of the adaptive model resulted in the establishment of coordination between Information Technology solutions and the organizational culture of organizations. It was also established that private organizations have achieved a better position of maturity due to their horizontal operating policies. The exploratory method has the perspective of pointing out important aspects of the problem and of finding the fundamental stages in an investigation, the data collection technique is the survey, to be able to interview and know the opinions of the people who work with technology and to be able to establish the most important data.
Keywords: business intelligence; organizational culture; information technology; politics